2016
DOI: 10.1186/s13643-016-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childcare and adiposity, body mass and obesity-related risk factors: protocol for a systematic review of longitudinal studies

Abstract: BackgroundThe rising prevalence of obesity, particularly in childhood, is a global public health emergency. There is some evidence that exposure to non-parental childcare before age 6 years is associated with subsequent development of obesity and obesity-related behaviours such as physical activity, sedentary behaviour, sleep, diet and stress, although these findings are inconsistent. It is possible that the relationship between early childcare and later obesity and obesity-related behaviours depends on charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…A recent study found that children spent more time being sedentary in childcare than at home . These previous studies have yielded mixed results; findings from a forthcoming systematic review will help clarify these relationships .…”
Section: Discussionmentioning
confidence: 96%
“…A recent study found that children spent more time being sedentary in childcare than at home . These previous studies have yielded mixed results; findings from a forthcoming systematic review will help clarify these relationships .…”
Section: Discussionmentioning
confidence: 96%
“…Globally, there has been a time shift in the BMI distribution and adiposity rebound timing. In Scotland, there has been a substantial shift of BMI distribution in the general population of a birth cohort born in 2004 compared with those born in 1990 [43]. A longitudinal study in Japan showed that the mean age of having minimal BMI was 4.8 years in boys and 4.7 years in girls born between 1995 and 1996 [5].…”
Section: Adiposity Rebound In 21st Century Childrenmentioning
confidence: 99%
“…In addition, we did not perform all aspects of searching and screening in duplicate which may have led to additional errors. We are currently conducting a systematic review examining the association of childcare factors with diet, physical activity, sedentary behavior, sleep, and stress that will help overcome these limitations [ 46 ]. We also restricted the review to longitudinal data in order to reduce the possibility of reverse causality [ 47 ].…”
Section: Discussionmentioning
confidence: 99%